Hemoglobin Constant Spring (Hb CS) Missed by HPLC in an Hb E Trait Pregnancy Resulting in Hb H-CS Disease in a Thai Girl: Utility of Capillary Electrophoresis - Pornprasert S. (2017)
© 2015, Indian Society of Haematology & Transfusion Medicine. Hemoglobin Constant Spring [Hb CS; α142, Term→Gln (TAA > CAA IN α2)] is often missed by routine laboratory testing, especially in subjects with co-inheritance of β-thalassemia or β-variants. We reported the case of a 1-year-old female with Hb H-CS disease who was born from a father with heterozygous of α-thalassemia-1 Southeast Asian type deletion and a mother with the combination of Hb CS and Hb E [β26 (B8) Glu→Lys, GAG > AAG] trait. A very tiny peak of Hb CS of the mother was easily ignored on the high performance liquid chromatography chromatogram while it was clearly seen on the capillary electrophoresis (CE) electrophoregram. Therefore, the CE is useful in screening for heterozygous Hb CS in a person with Hb E trait. This is of potential benefit for prevention of new cases of Hb H-CS disease.